2005
DOI: 10.2193/0022-541x(2005)69[1652:saaoci]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Activity Areas of Coyotes in the Bear River Mountains of Utah and Idaho

Abstract: We studied the seasonal movement patterns and dispersal of coyotes (Canis latrans) in the Bear River Mountains of northern Utah and southern Idaho to determine whether coyotes in this montane region exhibit an altitudinal migration on a seasonal basis. We used 3 locational parameters to assess whether a seasonal altitudinal migration was evident, including overlap in seasonal activity areas, distance between harmonic mean centers of activity, and seasonal differences in mean elevations of locations. Winter and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…winter centroids showed almost no relationship with the measures of altitudinal movement (Table 1). Horizontal movements have been the typical focus of seasonal movements of animals in mountain environments, including ibex (Parrini et al 2003, Grignolio et al 2004, mule deer (Nicholson et al 1997), roe deer (Mysterud 1999) sika deer (Igota et al 2004), elk and red deer (Hebblewhite et al 2006, Luccarini et al 2006) and coyotes (Canis latrans; Gantz and Knowlton 2005), even when altitudinal movement is considered to be the primary characteristic of these movements (Lovari et al 2006;chamois). Using horizontal distance would appear to be a poor measure upon which to base analysis of this phenomenon and may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…winter centroids showed almost no relationship with the measures of altitudinal movement (Table 1). Horizontal movements have been the typical focus of seasonal movements of animals in mountain environments, including ibex (Parrini et al 2003, Grignolio et al 2004, mule deer (Nicholson et al 1997), roe deer (Mysterud 1999) sika deer (Igota et al 2004), elk and red deer (Hebblewhite et al 2006, Luccarini et al 2006) and coyotes (Canis latrans; Gantz and Knowlton 2005), even when altitudinal movement is considered to be the primary characteristic of these movements (Lovari et al 2006;chamois). Using horizontal distance would appear to be a poor measure upon which to base analysis of this phenomenon and may be misleading.…”
Section: Discussionmentioning
confidence: 99%
“…It is unknown whether some jackals remain on small patches of high ground throughout the floods or whether they tend to migrate back and forth into these areas with the rising and receding flood waters. However, it seems likely that breeding jackals, similar to breeding (i.e., alpha) coyotes, do not establish territories where they cannot maintain them year round (Shivik et al 1996, Gantz andKnowlton 2005), particularly during pup rearing. Whelping of pups peaks in March and the young are unlikely to become independent before August-September when floodwaters are present.…”
Section: Seasonal Floodingmentioning
confidence: 99%
“…Flooding likely forces jackals and other carnivores to leave until after the waters recede. Breeding adults may not occur where they cannot be territorial throughout the year, as seems to be the case for the coyote (Shivik et al 1996, Gantz andKnowlton 2005). Alternatively, flooding may impact the postflood density of burrowing rodents, particularly the lesser bandicoot rat (Bandicota bengalensis), which is common throughout south Asia.…”
Section: Introductionmentioning
confidence: 99%
“…Activity patterns of coyotes (Canis latrans) have been reported in a variety of different habitats, but without considering activity patterns of their prey (Atwood et al, 2004;Fedriani et al, 2000;Gantz and Knowlton, 2005). Most reported that coyotes are active both day and night, with peaks of activity during crepuscular hours (Andelt, 1985;Gompper, 2002).…”
Section: Introductionmentioning
confidence: 99%